2012
DOI: 10.5923/j.plant.20120201.08
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Antimicrobial and Grain Protectant Activities of Clove Basil (Ocimum gratissimum L.) Grown in Nigeria

Abstract: Ocimum gratissimum Linn (Lamiaceae) is an herbaceous plant reputed for many medicinal and agronomic practices amongst Nigerian peasant farmers. O. gratissimum was investigated for antimicrobial activity against ten micro-organisms and for grain protectant activity against Callosobrochus maculatus. The phytocontituents of the aerial part of O. gratissimum were extracted with 95% ethanol using the percolation method. The crude ethanol extracted was further fractionated into hexane, chloroform and methanol fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…But the results are in confirmation with all other studies that show sensitivity of methanol extract to microorganisms (Ogunniran, K. O. (2009), Mann, A. (2012).…”
Section: Antimicrobial Activitysupporting
confidence: 81%
“…But the results are in confirmation with all other studies that show sensitivity of methanol extract to microorganisms (Ogunniran, K. O. (2009), Mann, A. (2012).…”
Section: Antimicrobial Activitysupporting
confidence: 81%
“…All tested basil genotypes showed different antibacterial potential due to high degree of variation in the chemical composition of basil extracts. Goyal andKaushik (2011) andMann (2012), reported results against similar pathogenic bacterial strains following treatment of extracts of different plants. This indicated that plant extracts contain essential compounds that retard or inhibit bacterial growth, breakage of cell membrane and make it permeable causing leakage of ions and molecules (Kamba and Hassan, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…These established a good support to the use of this plant in herbal medicine and as base for the development of new drugs and phytomedicine [21]. The study by Mann [7] showed that O. gratissimum extractants are potential sources of antimicrobial and preservative agents. In a study by Nweze and Eze [3], the extract of O. gratissimum showed good but varying in vitro activities against all the isolates tested including typed fungal strain of Candida albicans and Causative Agent of Pityriasis Versicolor in Rivers State, Nigeria (ATCC 90028).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known as Scent leaf or Clove basil and is found in many tropical countries. Africa and Asia are however, the two continents where most variants of the plant exists [3,[6][7]. O. gratissimum is found in the tropical and warm temperature regions such as India and Nigeria [8][9].…”
Section: Introductionmentioning
confidence: 99%